2009
DOI: 10.1021/ef9007032
|View full text |Cite
|
Sign up to set email alerts
|

Tar in Biomass Producer Gas, the Energy research Centre of The Netherlands (ECN) Experience: An Enduring Challenge

Abstract: Biomass gasification at temperatures below 1300 °C yields producer gas with a range of heavy hydrocarbons. These compounds, collectively known as tar, cause fouling and emission problems in equipment using the producer gas. This paper gives an overview of the work performed at the Energy research Centre of The Netherlands (ECN) on tar measurement, tar prevention, tar cracking, and tar removal. Much of the work has been performed in cooperation with partner institutes and industry. Measurement techniques discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(115 citation statements)
references
References 10 publications
(13 reference statements)
4
111
0
Order By: Relevance
“…With increasing temperature these functional groups are cleaved from the aromatic ring generating permanent gases CO, H 2 , CO 2 , CH 4 , C 2 H 4 and cyclopentadiene radicals, responsible for the increase of PAHs [45,46]. PAH tertiary tars (see Table A2) increased with temperature which is in accordance with observations reported in literature for magnesite in the same temperature range [47,48]. Increase of PAH tertiary tars could also be explained by the decomposition of the heavier GC undetectable fraction into lighter PAH tertiary tars [11].…”
Section: G/mol) To Benz[a]anthracene (M ≈ 22829 G/mol)supporting
confidence: 90%
See 1 more Smart Citation
“…With increasing temperature these functional groups are cleaved from the aromatic ring generating permanent gases CO, H 2 , CO 2 , CH 4 , C 2 H 4 and cyclopentadiene radicals, responsible for the increase of PAHs [45,46]. PAH tertiary tars (see Table A2) increased with temperature which is in accordance with observations reported in literature for magnesite in the same temperature range [47,48]. Increase of PAH tertiary tars could also be explained by the decomposition of the heavier GC undetectable fraction into lighter PAH tertiary tars [11].…”
Section: G/mol) To Benz[a]anthracene (M ≈ 22829 G/mol)supporting
confidence: 90%
“…Rabou et al [47] reported that Mg present in chicken manure ash was very active in cracking of 4 and 5-ring tar compounds even at 750°C.…”
Section: G/mol) To Benz[a]anthracene (M ≈ 22829 G/mol)mentioning
confidence: 99%
“…Tars can be defined as hydrocarbons with a molecular weight higher than benzene, and are a key impurity produced during the pyrolysis stage of the gasification process [234]. Their formation is heavily dependent on the nature of the gasification process, and thus preventing their formation by optimising this process is the best avenue for reducing tar levels.…”
Section: Gasification and Gas Clean-upmentioning
confidence: 99%
“…Some gas cleaning techniques include tar cracking, wet cleaning, the use of active carbon and ZnO [249]. Tar cracking techniques include catalytic cracking, thermal cracking, plasma cracking, scrubbing with water, and scrubbing with oil [234]. Wet gas cleaning is a conventional method where synthesis gas is in contact with fine droplets of water in a counter or co-current flow.…”
Section: Gasification and Gas Clean-upmentioning
confidence: 99%
“…In addition, several additional classifications for biomass tar exists in literature ( [16,18,19]). For example, the classification in primary, secondary, and tertiary tar (see [18]). Another approach was chosen by [8,17].…”
Section: Tar Sampling and Classificationmentioning
confidence: 99%